Life Skills Education through School-Based Management to Achieve National Education Goals - Jihan Jihan (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research examines life skills education implemented by schools with a school-based management approach to achieve national education goals. The purpose of this research is to know life skills education, school-based management and national education goals, as well as its application in the review of education management science. This research is descriptive qualitative because the data studied is not numerical. The results of this study are life skills education is education in education units based on the local wisdom of education units, so that students get provisions for life in accordance with what is in their environment, school-based management is management autonomy that authorizes schools to develop local curriculum based on needs, the purpose of education in accordance with the national education system law is to educate the nation's life. The application of life skills education through school-based management is a system of policy independence by schools in conducting input, process, and output of students in accordance with the objectives of the institution to provide life skills to students according to their needs.